2012
DOI: 10.1111/jcpe.12038
|View full text |Cite
|
Sign up to set email alerts
|

Salivary biomarkers of oral health – a cross‐sectional study

Abstract: This investigation shows that IL-1β, MMP-8 and the ratio of MMP-8/TIMP-1 could be used as markers of periodontal disease in larger patient populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
171
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 152 publications
(189 citation statements)
references
References 45 publications
15
171
3
Order By: Relevance
“…However, there is only one previous study where low salivary flow rate has been indicated as a predictive factor for high salivary MMP-8 counts [Collin et al, 2000]. Rathnayake et al [2013a] found a weak correlation between BOP and MMP-8 levels using the same material as the current study. The correlation was not mirrored in the current study, which may be explained by the use of different statistical models for the analysis of the material.…”
Section: Discussioncontrasting
confidence: 38%
See 2 more Smart Citations
“…However, there is only one previous study where low salivary flow rate has been indicated as a predictive factor for high salivary MMP-8 counts [Collin et al, 2000]. Rathnayake et al [2013a] found a weak correlation between BOP and MMP-8 levels using the same material as the current study. The correlation was not mirrored in the current study, which may be explained by the use of different statistical models for the analysis of the material.…”
Section: Discussioncontrasting
confidence: 38%
“…The methodological descriptions below regarding participants, clinical and radiographic examination, saliva sampling and biomarker analysis have been described in previous articles [Lundegren et al, 2012;Rathnayake et al, 2013a].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…found to differentiate between periodontal health and the conditions of gingivitis and periodontitis 13,14 and plays an important role in periodontal tissue destruction. 13 Furthermore, especially serum MMP-8 and TIMP-1 levels may reflect systemic chronic inflammatory and immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…Salivary biomarkers are used for screening purposes in epidemiological studies [13] and are being used to monitor and detect various diseases, such as breast cancer [14], lung cancer [15], celiac disease [16], and chronic renal failure [11]. With regard to oral health, three important salivary variables should be investigated: pH, flow velocity, and buffering capacity.…”
Section: Discussionmentioning
confidence: 99%